MODERN TECHNOLOGIES OF TREATMENT AND PROPHYLAXIS OF ANTIBIOTIC-ASSOCIATED DIARRHEA IN CHILDREN - A.N. Surkov (Вопросы современной педиатрии, 2011)
Intestinal microflora derangement is quite common among children with various somatic abnormalities. Jne of the most common reasons for disbacteriosis development — antibiotic therapy. The vast majority of antibiotics affects gastrointestinal microflora that leads to dyspeptic syndrome development and so-called antibiotic-associated diarrhea. Intestinal disbacteriosis affects homeostasis, leading to considerable shifts in the state of different systems and organs. That’s why correction and prophylaxis of intestinal disbacteriosis against the background of antibiotic treatment is quite important for a pediatrician. This article contains main information upon epidemiology, pathogenesis, clinical forms and clinical presentation, diagnostics and treatment of antibiotic-associated diarrhea among children. Key words: indigenous intestinal microflora, antibiotic-associated diarrhea, treatment, prophylaxis, ecoantibiotics, children. (Voprosy sovremennoi pediatrii — Current Pediatrics. — 2011; 10 (5): 146–151.)